Occurrence of Honey Bee (Apis mellifera L.) Pathogens in Wild Pollinators in Northern Italy - Cilia, Giovanni; Flaminio, Simone; Zavatta, Laura; Ranalli, Rosa; Quaranta, Marino; Bortolotti, Laura; Nanetti, Antonio (Frontiers in Cellular and Infection Microbiology, 2022)
Diseases contribute to the decline of pollinator populations, which may be aggravated by the interspecific transmission of honey bee pests and pathogens. Flowers increase the risk of transmission, as they expose the pollinators to infections during the foraging activity. In this study, both the prevalence and abundance of 21 honey bee pathogens (11 viruses, 4 bacteria, 3 fungi, and 3 trypanosomatids) were assessed in the flower-visiting entomofauna sampled from March to September 2021 in seven sites in the two North-Italian regions, Emilia-Romagna and Piedmont. A total of 1,028 specimens were collected, identified, and analysed. Of the twenty-one pathogens that were searched for, only thirteen were detected. Altogether, the prevalence of the positive individuals reached 63.9%, with Nosema ceranae, deformed wing virus (DWV), and chronic bee paralysis virus (CBPV) as the most prevalent pathogens. In general, the pathogen abundance averaged 5.15 * 106 copies, with CBPV, N. ceranae, and black queen cell virus (BQCV) as the most abundant pathogens, with 8.63, 1.58, and 0.48 * 107 copies, respectively. All the detected viruses were found to be replicative. The sequence analysis indicated that the same genetic variant was circulating in a specific site or region, suggesting that interspecific transmission events among honey bees and wild pollinators are possible. Frequently, N. ceranae and DWV were found to co-infect the same individual. The circulation of honey bee pathogens in wild pollinators was never investigated before in Italy. Our study resulted in the unprecedented detection of 72 wild pollinator species as potential hosts of honey bee pathogens. Those results encourage the implementation of monitoring actions aiming to improve our understanding of the environmental implications of such interspecific transmission events, which is pivotal to embracing a One Health approach to pollinators’ welfare.